A case of delayed neurological manifestation following carbon monoxide poisoning in Sri Lanka: epidemiology of exposure and literature review - Prabhashini Kumarihamy; Senanayake Abeysinghe Mudiyanselage Kularatne; Manoji Pathirage; Wasala Mudiyanselage Sujeewa Nilanthi Gunaratne; Roshita Waduge (BMC, 2019)
Abstract Background Carbon monoxide poisoning is a common emergency worldwide, which carries high morbidity and mortality. Some patients who recover from the insult of acute carbon monoxide toxicity may later develop delayed neuropsychiatric sequelae (DNS) after a lucid period in the form of cognitive impairments, a broad spectrum of neurological deficits and affective disorders. Here, we present the first case of DNS following carbon monoxide poisoning in Sri Lanka and epidemiology of the exposure of nine (9) more victims. Case presentation A 55-year-old patient and nine other people developed effects of carbon monoxide poisoning in two different occasions after sleeping few hours in the same room in their work place in Sri Lanka. These patients developed spectrum of symptoms with the acute carbon monoxide poisoning. However, one patient developed neurological deterioration pertaining to delayed neuropsychiatric sequelae (DNS) after 1 month of lucid interval. His MRI scan of the brain showed diffuse high signal intensity involving subcortical white matter, globus pallidus on FLAIR and T2W images. These areas showed high signals in DWI images with no significant changes appreciated on ADC map. There was no abnormal contrast enhancement appreciated in the above areas. EEG showed generalized slow waves. He gradually deteriorated over next 2 weeks, exhibited athetoid movements of his feet and hands and went into rigid akinetic mute state. He could not response to any stimulation and even displayed decorticated-like posture and died. Others had normal MRI brain finding at 8 weeks of acute toxicity and all were neurologically normal after 1 year. Conclusion Though, it is uncommon in a tropical country like Sri Lanka, clinicians should have high degree of suspicion with the correct circumstances, as it is a challenge for the emergency physicians, even in countries with higher rate of CO poisoning. The exact mechanisms of acute and delayed toxicity, preventive methods and the suggested treatments are yet to be elucidated and this needs further attention and studies.